Clinical implications of E-cadherin associated hereditary diffuse gastric cancer. Issue 6 (11th May 2004) - Fitzgerald, R C; Caldas, C
Abstract : Approximately 1–3% of gastric cancers arise as a result of inherited gastric cancer predisposition syndromes. These may be of the diffuse or intestinal type. Linkage analysis has recently implicated E-cadherin mutations in an estimated 25% of families with an autosomal dominant predisposition to diffuse type gastric cancers. This subset of gastric cancer has been termed hereditary diffuse gastric cancer (HDGC).